2020
DOI: 10.1007/s10853-020-04632-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite coatings obtained by electrophoretic co-deposition of poly(etheretherketone)/graphene oxide suspensions

Abstract: Nanocomposite coatings were successfully prepared by electrophoretic deposition of poly(etheretherketone) (PEEK)/graphene oxide (GO) suspensions. The GO flakes developed a large-scale co-continuous morphology with the basal plane mainly aligned with the coating surface. However, the PEEK particles were also found to be wrapped by GO nanosheets when deposited on the stainless steel substrate. Both phenomena, the co-continuous morphology and the wrapping effect, were dependent on the initial GO content in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 95 publications
(131 reference statements)
1
13
0
Order By: Relevance
“…Uniform coatings were deposited via DC-EPD. The coatings were subsequently dried at 150 • C, and sintered at 380 • C. It was shown that uniform coatings can be obtained by following the scheme presented in Figure 21 [103]. Similarly, PEEK/GO composite coatings were uniformly deposited via EPD.…”
Section: Epd Of Peek Based Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Uniform coatings were deposited via DC-EPD. The coatings were subsequently dried at 150 • C, and sintered at 380 • C. It was shown that uniform coatings can be obtained by following the scheme presented in Figure 21 [103]. Similarly, PEEK/GO composite coatings were uniformly deposited via EPD.…”
Section: Epd Of Peek Based Coatingsmentioning
confidence: 99%
“…The coatings were subsequently dried at 150 °C, and sintered at 380 °C. It was shown that uniform coatings can be obtained by following the scheme presented in Figure 21 [103]. Although the challenge of the deposition of PEEK-based composite coatings was solved through the choice of relevant solvent and tuning deposition parameters, PEEKbased composite coatings require sintering to achieve the appropriate adhesion strength and wettability.…”
Section: Epd Of Peek Based Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-ether-ether-ketone (PEEK) is a kind of semi-crystalline aromatic thermoplastics with outstanding features, such as excellent mechanical properties [1,2] (young's modulus, 4 GPa; tensile strength, 150 MPa), thermal stability [3,4] (glass transition temperature, 143°C; melting point 343°C; decomposition temperature, 580 °C), radiation resistance [5,6] (1100 M γ radiation without significant degradation) and chemical corrosion resistance [7][8][9][10], which make it attractive to the fields of medical and health, as well as aerospace [11][12][13][14][15][16]. However, it is usually necessary to have superior conductivity on the surface to meet the electrical properties of the products when they are applied, which is contrary to the high insulation properties of the polymers, such as PEEK.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique properties of PEEK, the EPD of both PEEK [ 11 , 12 , 13 , 14 ] and PEEK-based [ 6 , 15 , 16 , 17 , 18 , 19 ] composite coatings has been widely studied, also with respect to improving the tribological properties of metallic materials. In our previous works, we have shown that it is possible to fabricate repeatable and homogeneous, semi-crystalline or amorphous PEEK [ 20 ] and composite PEEK-based coatings [ 21 , 22 , 23 , 24 , 25 ] using EPD and post-EPD heat treatment.…”
Section: Introductionmentioning
confidence: 99%